(untitled) (Semiárida, 2018)
The aim of the survey was to evaluate the efficiency of two methods for the determination of available P and the effect of fertilization with solid and liquid P sources on corn and soybean crops in soils with calcium carbonates. A field experiment near general Pico (La Pampa) was used where during two crop seasons early and late planted corn and in one season two maturity groups of soybean were fertilized with triple superphosphate (TSP) and ammonium polyphosphate (APP) at 40 kg.ha-1 of P2O5. The available P was determined with Bray-Kurtz 1 and Olsen extractions, and the yield was recorded in all treatments. The results showed no response to P addition except in two fertilized treatments with TSP (one late corn crop and in the group 4 soybean cultivar). This was particularly true for POlsen, while for Bray-Kurtz 1 the differences were less. These results indicated that the soils solubilized sufficient quantities of P to satisfy the requirements of corn and soybean and no differences between the two sources was found. DOI: http://dx.doi.org/10.19137/semiarida.2017(01).11-18